HISTORY OF DEVELOPMENT OF NATIONAL POLICY AND ETHNIC IDENTITY IN THE REPUBLIC OF KAZAKHSTAN - Turlybekova A. M.; Shamshudinova G. T. (Scientific Journal of Pedagogy and Economics, 2021)
This article discusses the modern world as the kind of ethnic explosion, the concrete manifestations of which are the growth of the significance of ethnic identity, increasing people’s interest in their roots, traditions, culture and history. The demand for social balance related to ethnic and cultural specifics has noticeably revived. We can say that ethnic communities are real, stable historical formations, and ethnicity is an important, constantly acting factor of the social development. At different times it manifests in different ways, in the situation of serious social transformations that we are currently experiencing, there is the surge in ethnicity. These contradictions are reflected in the Republic of Kazakhstan due to its multinational composition. On the one hand, there are processes of forming the single identity instead of the national identity, based on the citizenship, and on the other hand, there is growing interest in the national culture and traditions. In the modern society people have the right to choose their ethnic selfdetermination and freedom of self-identification with the particular ethnic and national community, which is guaranteed by the Constitution of the Republic of Kazakhstan.